Bound immunoglobulin and foreign antigen in lungs of sudden infant death syndrome victims. - Ackermann, W W (1979)
Lung sections from 33 infants who died suddenly and unexpectedly and were diagnosed by medical examiners as sudden infant death syndrome (SIDS) gave evidence of bound immunoglobulin G (IgG) when examined by direct fluorescent antibody technique. Ten tissues from appropriate control infants were negative. Specimens containing IgG exhibited no IgA or IgE, but three contained IgM. Sixty-one percent of lung sections with IgG contained either K or lambda antigens; the remainder contained both. The indirect fluorescent antibody technique gave similar results. Blood sera of some individuals in the study which were tested all contained both K and lambda antigens. Fluorescent-labeled immunoglobulin from one SIDS victim stained 7 of 17 SIDS lung sections tested, including his own. Labeled immunoglobulin from three mothers of SIDS victims exhibited differential selectivity in reaction with antigen in lungs of a group of 18 SIDS infants. They did not react with 10 control infant tissues. Various labeled adult sera, cord sera, and serum from an apneic child did not react with the various lungs of SIDS victims in the study.